Diachronic study of changes in vegetal cover in a mountainous ecosystem by spatial remote sensing: case of the Aures mountains (Algeria) - Abbas, Saliha (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Since the 1970s, arid and semi-arid zones, as one of the most vulnerable ecosystems, have attracted considerable attention. The the study of the influences of climate variations and human activities in this zone have become, and being the hot topics in the field of ecological environment research. A better understanding of the evolution of land use patterns and plant cover is a major concern for countries whose ecosystems are undergoing severe degradation. Indeed, land use dynamics have direct implications on the availability of natural resources. spatial remote sensing provides an extremely effective tool for locating problems and monitoring developments, our study carried out on the Aures Mountains in eastern Algeria, using the normalized difference vegetation index (NDVI), highlights the extent of changes in vegetation cover between 2000 and 2023, 80815,25 ha of the vegetal cover witnessed a regression between 2000 and 2023, or the area lost 3513,706 ha of vegetation the per year. A pronounced regressive evolution of the plant cover is observed in the southwest and northeast of the Aures mountains, particularly in the "forest of Beni Oudjana, Beni Melloul and Ouled Yaakoub", in the municipalities of Chelia, Bouhmama and M'sara. The main factors contributing to the decline in plant cover are: deforestation, overgrazing, forest fires and the resulting water erosion.